Digital Augmented Reality Flipbook Based on Local Wisdom: An Instructional Innovation to Enhance Students' Mathematical Literacy - Lestari, Fitria; Noprisa, Noprisa; Cahyani, Jeshinta Dwi; Wibowo, Deni Sapto (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2026)
This research aims to develop and evaluate the effectiveness of a Flipbook Augmented Reality (AR) application based on local wisdom from Lampung in enhancing students' mathematical literacy in geometry topics. The method used is a developmental study with a design research approach, employing the 1993 Tessmer model, which consists of the preliminary, formative evaluation, and prototyping, including three parts: expert review, one-to-one, and small group, followed by the field test stage. The subject of the study was an eighth-grade student at Junior High School in Bandar Lampung. The instruments used were mathematical literacy tests and student response questionnaires. The results of expert validation indicate that the product falls into the excellent category, with a practicality level reaching 83.1%. The results of the binomial test show that more than 70% of students achieved learning mastery. The highest achievement in mathematical literacy was found in the communication indicator (88.15%). The research has proven effective in improving students’ mathematical literacy. Flipbook AR can serve as a contextual learning alternative that integrates technology and local culture to meaningfully reinforce students' understanding of mathematical concepts.